Innovations in practice and service delivery across the lifespan - Biegel, David E.; Blum, Arthur (New York : Oxford University Press, 1999)
This text will introduce practitioners and students to recent strategies and innovations to effectively deal with a range of problems across the lifespan such as homelessness, alcohol and drug abuse, teen violence and mental illness.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- United States; Medical social work -- United States; Medical care -- United States